Alternatives for the worse: Molecular insights into adverse effects of bisphenol a and substitutes during human adipocyte differentiation. (November 2021) - Schaffert, Alexandra; Krieg, Laura; Weiner, Juliane; Schlichting, Rita; Ueberham, Elke; Karkossa, Isabel; Bauer, Mario; Landgraf, Kathrin; Junge, Kristin M.; Wabitsch, Martin; Lehmann, Jörg; Escher, Beate I.; et al.
Highlights: BPA and its emerging substitutes BPAF, BPB, BPF, BPS antagonized human PPARγ. BPA and substitutes decreased adipogenesis of human preadipocytes. Proteomics revealed adipocyte dysfunction and increased inflammatory pathways. BPA, BPB, and BPS significantly reduced insulin sensitivity upon insulin stimulation. Substitute effects were similar to BPA at environmentally relevant concentrations. Abstract: Bisphenol A (BPA), which is used in a variety of consumer-related plastic products, was reported to cause adverse effects, including disruption of adipocyte differentiation, interference with obesity mechanisms, and impairment of insulin- and glucose homeostasis. Substitute compounds are increasingly emerging but are not sufficiently investigated. We aimed to investigate the mode of action of BPA and four of its substitutes during the differentiation of human preadipocytes to adipocytes and their molecular interaction with peroxisome proliferator-activated receptor γ (PPARγ), a pivotal regulator of adipogenesis. Binding and effective biological activation of PPARγ were investigated by surface plasmon resonance and reporter gene assay, respectively. Human preadipocytes were continuously exposed to BPA, BPS, BPB, BPF, BPAF, and the PPARγ-antagonist GW9662. After 12 days of differentiation, lipid production was quantified via Oil Red O staining, and global protein profiles were assessed using LC-MS/MS-based proteomics. All tested bisphenols bound to human PPARγ with similar efficacy as the natural ligand 15d-PGJ2 in vitro and provoked an antagonistic effect on PPARγ in the reporter gene assay at non-cytotoxic concentrations. During the differentiation of human preadipocytes, all bisphenols decreased lipid production. Global proteomics displayed a down-regulation of adipogenesis and metabolic pathways, similar to GW9662. Interestingly, pro-inflammatory pathways were up-regulated, MCP1 release was increased, and adiponectin decreased. pAKT/AKT ratios revealed significantly reduced insulin sensitivity by BPA, BPB, and BPS upon insulin stimulation. Thus, our results show that not only BPA but also its substitutes disrupt crucial metabolic functions and insulin signaling in adipocytes under low, environmentally relevant concentrations. This effect, mediated through inhibition of PPARγ, may promote hypertrophy of adipose tissue and increase the risk of developing metabolic syndrome, including insulin resistance.